Functional dependence and nutritional status among leprosy survivors in Sungai Buloh, Malaysia / Mohamad Rodi Isa, Siti Munira Yasin and Mohammad Idris Zamhuri - Isa, Mohamad Rodi; Yasin, Siti Munira; Zamhuri, Mohammad Idris (Faculty of Medicine, 2016)
Introduction: Leprosy is a chronic granulomatous disease which also known as Hansen’s disease caused by Mycobacterium leprae. The social rights and health requirements should not be neglected among the remaining survivors. Although nutritional status and leprosy invasion has been studied in the past, there is still an unclear relationship between these two. The aim of this study was to assess the relationship between nutritional status and disability among the leprosy survivors. Methods: A community based, cross-sectional study using convenience sampling was conducted at Sungai Buloh, Selangor area from June 2014 to July 2014. The degree of disability was assessed using Barthel’s Index and the nutritional status assessment was assessed using Mini Nutritional Assessment. The data was analysed using SPSS version 20. Results: A total of 73 patients were involved in the study (60.3% were male and 89.0% were Chinese). The prevalence of disability was 56.2% (95% CI: 44.5 – 67.8) with walking up-stair was the highest item that need help (50.7%). There were 9.6% malnourished and 49.3% were at risk of malnutrition. There was a negative strong correlation between Nutritional score and the Barthel’s index score (Spearman rho, ρ = -0.714, p < 0.001). Conclusions: Measures must be taken to improve their nutritional status in order to increase their ability to be more independent particularly those who are very old. The degree of disability increases with malnutrition.